2013
DOI: 10.1097/shk.0b013e3182a5175b
|View full text |Cite
|
Sign up to set email alerts
|

Can Peripheral Blood Mononuclear Cells be Used as a Proxy for Mitochondrial Dysfunction in Vital Organs During Hemorrhagic Shock and Resuscitation?

Abstract: INTRODUCTION-Although mitochondrial dysfunction is thought to contribute to the development of post-traumatic organ failure, current techniques to assess mitochondrial function in tissues are invasive and clinically impractical. We hypothesized that mitochondrial function in peripheral blood mononuclear cells (PBMCs) would reflect cellular respiration in other organs during hemorrhagic shock and resuscitation (HS&R).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…permeabilized RBCs vs. permeabilized muscle; our attempts to permeabilize RBCs were not successful), we showed that mitochondrial parameters measured in intact RBCs moderately correlated to those measured in permeabilized pectoral muscle fibres (see Table 3 for details). Interestingly, similar findings have been found in humans between blood mononuclear cells and organs such as kidney and heart (Karamercan et al 2013). Altogether, it indicates that mitochondrial parameters are to some extent correlated among tissues, including blood.…”
Section: O R R E L a T I O N S B E T W E E N M I T O C H O N D R I supporting
confidence: 82%
See 1 more Smart Citation
“…permeabilized RBCs vs. permeabilized muscle; our attempts to permeabilize RBCs were not successful), we showed that mitochondrial parameters measured in intact RBCs moderately correlated to those measured in permeabilized pectoral muscle fibres (see Table 3 for details). Interestingly, similar findings have been found in humans between blood mononuclear cells and organs such as kidney and heart (Karamercan et al 2013). Altogether, it indicates that mitochondrial parameters are to some extent correlated among tissues, including blood.…”
Section: O R R E L a T I O N S B E T W E E N M I T O C H O N D R I supporting
confidence: 82%
“…Interestingly, similar findings have been found in humans between blood mononuclear cells and organs such as kidney and heart (Karamercan et al . ). Altogether, it indicates that mitochondrial parameters are to some extent correlated among tissues, including blood.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have shown that mitochondrial function measured in blood cells is correlated to some extent to mitochondrial function in other tissues such as kidneys, heart, skeletal muscles and brain (e.g. [22,[37][38][39], while some other studies did not find any significant relationship (e.g. [40]).…”
Section: High-resolution Respirometry Analysis Of Mitochondrial Function In Intact Blood Cellsmentioning
confidence: 98%
“…As such, there is considerable interest in more direct measures of mitochondrial dysfunction. Peripheral blood mononuclear cells (PBMCs) have often been used for this purpose (10)(11)(12)(13)(14), as they provide an accessible source of mitochondria, have demonstrated moderate correlation with mitochondrial changes in other organ systems (15), and are directly involved in the immuno-inflammatory response characteristic of sepsis and other illnesses (3,16,17). However, PBMCs are a heterogenous mixture of lymphocyte and monocyte subtypes with variable metabolic profiles.…”
Section: Introductionmentioning
confidence: 99%